Canine cancer immunotherapy studies: linking mouse and human. Issue 1 (20th December 2016) - Park, Jiwon S.; Withers, Sita S.; Modiano, Jaime F.; Kent, Michael S.; Chen, Mingyi; Luna, Jesus I.; Culp, William T. N.; Sparger, Ellen E.; Rebhun, Robert B.; Monjazeb, Arta M.; Murphy, William J.; Canter, Robert J.
Abstract : Despite recent major clinical breakthroughs in human cancer immunotherapy including the use of checkpoint inhibitors and engineered T cells, important challenges remain, including determining the sub-populations of patients who will respond and who will experience at times significant toxicities. Although advances in cancer immunotherapy depend on preclinical testing, the majority of in-vivo testing currently relies on genetically identical inbred mouse models which, while offering critical insights regarding efficacy and mechanism of action, also vastly underrepresent the heterogeneity and complex interplay of human immune cells and cancers. Additionally, laboratory mice uncommonly develop spontaneous tumors, are housed under specific-pathogen free conditions which markedly impacts immune development, and incompletely model key aspects of the tumor/immune microenvironment. The canine model represents a powerful tool in cancer immunotherapy research as an important link between murine models and human clinical studies. Dogs represent an attractive outbred combination of companion animals that experience spontaneous cancer development in the setting of an intact immune system. This allows for study of complex immune interactions during the course of treatment while also directly addressing long-term efficacy and toxicity of cancer immunotherapies. However, immune dissection requires access to robust and validated immune assays and reagents as well as appropriate numbers for statistical evaluation. Canine studies will need further optimization of these important mechanistic tools for this model to fulfill its promise as a model for immunotherapy. This review aims to discuss the canine model in the context of existing preclinical cancer immunotherapy models to evaluate both its advantages and limitations, as well as highlighting its growth as a powerful tool in the burgeoning field of both human and veterinary immunotherapy.